Desarrollo socioemocional en niños de 4 a 5 años de la unidad educativa “Hermano Miguel” - Carrión Ortega, Paula Manoli (2023)
The present research is oriented to diagnose the following problem: to stimulate the socioemotional development in children from 4 to 5 years old in the Educational Unit "Hermano Miguel" for which it projects as objective: To diagnose the socioemotional development in children from 4 to 5 years old in the Educational Unit "Hermano Miguel", for the improvement of coexistence. The work was based on the qualitative approach and documentary bibliographic research. We took into account the survey and the scale, which allowed us to give validity and reliability to our project, helping to carry out the diagnosis; giving as a result in the questionnaire that 93% of parents apply communication and help their children in their socioemotional development, as for the scale with the children gave us 84% that children do not know how to control their emotions and socialize. To conclude, it can be said that the children of the "Hermano Miguel" Educational Unit, initial II, do not have a good socioemotional development because they do not know how to coexist and control their emotions, with a small percentage of children who do have a good socioemotional development, so it is advisable to apply playful activities in green and wide spaces that improve their sociability and their emotions.